Improved Antioxidant Activity of Low-Fat Herb-Fortified Cottage Cheese - Setyawardani, Triana; Sumarmono, Juni; Dwiyanti, Hidayah; Rizqiati, Heni; Arkan, Naofal Dhia; A. Mohamed, Tasnim Hunin (Buletin Peternakan, 2024)
This study aimed to evaluate the properties of low-fat cottage cheese with the addition of herbs. We conducted an experiment with nine treatments, namely P1: whole-milk cottage cheese; P2: low-fat cottage cheese; P3: low-fat cottage cheese + 20% bidara leaf extract; P4: low-fat cottage cheese + 20% bay leaf extract; P5: low-fat cottage cheese + 20% moringa oleifera leaf extract; P6: Low-fat cottage cheese + 10% bidara leaf extract + 10% bay leaf extract; P7: low-fat cottage cheese + 10% bidara leaf extract + 10% moringa oleifera leaf extract; P8: low-fat cottage cheese + 10% bay leaf extract + 10% moringa oleifera leaf extract; and P9: low-fat cottage cheese + 6.67% bidara leaf extract + 6.67% bay leaf extract + 6.67% moringa oleifera leaf extract. The microbial profile of cheese showed that the total LAB count was retained at 6.23-7.25 log CFU/g. While herb-fortified cottage cheese contained a significantly higher level of antioxidants, the lowest cholesterol level was observed in cottage cheese fortified with 20% bidara leaf extract. The general fatty acids in cheese without herb addition were saturated fatty acids (51.94%) and unsaturated fatty acids (15.67%), with palmitic acid being the most predominant fatty acid (36.62%). In conclusion, herbs can improve antioxidant levels and retain total fatty acid in low-fat cottage cheese.